Medical health insurance: a cross-sectional study of factors associated with the final year undergraduate student's intention / Muhammad Danial Kamarulzaman ... [et al] - Kamarulzaman, Muhammad Danial; Rabun, Mohd Nazir; Mohd Halim, Mustaqim (Universiti Teknologi MARA, Kedah, 2022)
Medical and health insurance is crucial nowadays than it ever was. Lifestyle of people keep on changing from time to time in their daily activities. Malaysian government has taken a step forward regarding the health insurance by planning in launching insurance scheme for its people that have difficulties in paying the premium. However, the level of awareness and inclination towards medical health insurance was still at its lowest level. Thus, the study tries to examine the medical health insurance intentions among final year students and its correlated variables between knowledge, social influence, financial literacy and product attributes factors. Relationships between these factors were examined and analyzed. Results shows that all factors are found to correlate significantly with their level of medical health insurance intentions. Surprisingly, findings found that most of the students had a high level of medical health insurance intentions. This study is crucial in increasing the awareness and intention of final year students to purchase medical health insurance after they have graduated from the universities.